Bacterial lipopolysaccharide potentiates type II collagen-induced arthritis in mice - Robert G. Caccese; John L. Zimmerman; Richard P. Carlson (Hindawi Limited, 1992)
Collagen-induced arthritis (CIA) is an immunologically relevant animal model of human rheumatoid arthritis. Studies comparing the disease incidence in genetically susceptible male and female DBA/1LacJ mice demonstrated that under low density/low stress housing conditions, female mice had earlier onset (day 35) and higher disease incidence (25%) than the male mice (17% at day 49) when immunized with bovine type II collagen. A single subcutaneous or intraperitoneal injection of bacterial lipopolysaccharide (LPS) 17-24 days after collagen immunization greatly potentiated this standard CIA model in a dose related manner. 20-40 μg of LPS accelerated the onset of disease from day 35 to day 21 and exacerbated the clinical severity score from 0.27 to 2.00 at day 42. A similar administration of 6 μg of recombinant interleukin-β produced a comparable potentiated CIA model. The acute phase protein, serum amyloid P (SAP), was elevated in the serum at day 26 to 440 μg ml−1 for the LPS potentiated CIA mice compared to 65 μg ml−1 in the non-potentiated immunized CIA mice. There was a significant correlation (r = 0.78) between SAP levels and disease expression in the LPS treated CIA mice. The rapidity and uniformity of disease expression in this LPS potentiated CIA model will allow more and different drugs to be evaluated with a smaller number of animals.